Use of Bully Box Media to Prevent Bullying Cases in Schools in Cipancuh Village - Melisa Maharani (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
Bullying at SDN 1 Cipancuh, Cipancuh Village, Indramayu, is an issue that needs to be addressed immediately due to its widespread negative impacts, ranging from mental health problems (low self-esteem, fear) to decreased learning motivation and student attendance rates. This Community Service Program (KKN) activity primarily aims to measure and improve sixth grade students' understanding of the dangers of bullying and train them in self-prevention strategies and positive interventions. The method applied is Classical Guidance (Socialization) combined with the innovative media Bully Box Game, a role-playing simulation that educates participants on how to fight bullying without violence. The program targets 21 sixth grade students. Evaluation of the program's effectiveness was conducted through quantitative Pre-test and Post-test instruments. The results of the data analysis showed a very significant increase in understanding, with the average score of participants increasing from 66.7 to 90.5. The Normalized Gain (⟨g⟩) analysis averaged 0.8 (or 79.4%), which is statistically classified as Highly Effective. These findings confirm that an educational approach combined with interactive simulations is highly effective in transferring anti-bullying knowledge in a short time. This program is recommended to be integrated into school policies to create a child-friendly and bullying-free learning environment.